ANALISIS ISI NASKAH BERITA SISWA JURUSAN PRODUKSI SIARAN PERTELEVISIAN SMK NEGERI 5 PALEMBANG - Junia Astuti (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to determine the Content Analysis of News Manuscripts for Students of theTelevision Broadcast Production Department, SMK Negeri 5 Palembang. The research methodused is descriptive qualitative research. Data collection techniques used observation, interviewsand documentation. The data sources for this research were class XI students majoring in PSPT,mass communication teachers and heads of departments. The data analysis technique uses contentanalysis using Holsti's theory. The results of this study are that students have been able to makenews scripts, in accordance with news script writing techniques, for the type of news that studentsmake is the type of news reports directly about an event (straight news) then for development effortscarried out by the school, namely first preparing educators according to the needs of thedepartment, secondly by providing adequate internet facilities, thirdly by providing space (schoollaboratories and cinemas), fourthly by facilitating participation in various competitions, and fifthlyby forming journalism extracurriculars as a place to develop students' talents and interests, thesixth available library room various types of literacy.